Differences in Technical Components for Each Playing Position in Basketball Athletes - Rismayadi, Alen; M. Syahid, Angga (Universitas Pendidikan Ganesha, 2023)
Basketball is a team sport that requires good technical components. Meanwhile, research that reveals technical components based on playing positions is still minimal. Therefore, through this research, researchers want to identify technical components based on point guard, shooting guard, small forward, power forward, and center playing positions. The research method is quantitative descriptive research with a retrospective causal comparative design or ex-post factor design. The research subjects were 20 male basketball athletes and 20 female basketball athletes, consisting of 8 point guards, 8 shooting guards, 8 small forwards, 8 power forwards, and 8 centers. The instruments used are the Passing Skills Test, the Under Ring Skills Test, the Shooting Skills Test, the Lay Up Shoot Skills Test, and the Dribbling Skills Test. After the data was collected, data analysis was one-way ANOVA using SPSS for calculations. The results of the research show that there are differences in the techniques for each playing position in basketball athletes.